Cryotop Vitrification as Compared to Conventional Slow Freezing for Human Embryos at the Cleavage Stage: Survival and Outcomes - Tseng-Kai Lin; Jin-Tsung Su; Fa-Kung Lee; Yu-Ru Lin; Hsiao-Ching Lo (Elsevier, 2010)
Objective: This study was conducted to compare the efficacy of cryotop vitrification of human cleavage-stage embryos to that of conventional slow freezing of these embryos with respect to survival. A second objective was to compare the two cryopreservation techniques with respect to outcomes for a cohort of women. Materials and Methods: Cleavage-stage embryos from 102 patients were cryopreserved either by vitrification (57 patients) or by traditional slow freezing (45 patients). After thawing, rates of embryo survival, implantation, and clinical pregnancy were determined. Results: Survival of embryos was significantly higher with the vitrification procedure as compared to traditional slow freezing [287/298 (96.3%) vs. 294/446 (65.9%); p < 0.05). Rates of implantation and clinical pregnancy were also significantly higher using vitrification procedure as compared to the slow freezing procedure (24.3% vs. 7.1% and 35.6% vs. 15.6% respectively, p < 0.05). Conclusion: As compared to conventional slow freezing, cryopreservation of human cleavage-stage embryo using vitrification results in higher rates of embryo survival, implantation, and clinical pregnancy. Vitrification therefore represents the superior cryopreservation technique for cleavage-stage embryos.